Approximation by Durrmeyer Type Exponential Sampling Operators. (2nd January 2022) - Bajpeyi, Shivam; Kumar, A. Sathish; Mantellini, Ilaria
Abstract: In the present article, we derive some approximation results concerning the order of convergence for a family of Durrmeyer type exponential sampling operators. Further, we improve the rate of approximation by constructing linear combinations of these operators. At the end, we provide a few examples of the kernel functions to which the presented theory can be applied along with the graphical representation.